Respuesta :
Answer:
Second option
Third option
Last option
Step-by-step explanation:
You have the expression [tex]3x - 12 - 2(x + 12)[/tex], you can find the following equivalent expressions:
Apply Distributive property:
[tex]3x - 12 - 2x -24[/tex]
Group the first two terms and factor out 3:
[tex]=3(x - 4) - 2x -24[/tex] (Second option)
Apply Distributive property and then add the like terms:
[tex]=3x - 12 - 2x - 24[/tex]
[tex]=x-36[/tex] (Last option)
Group the first two terms and factor out 3:
[tex]=3(x - 4) - 2(x + 12)[/tex] (Third option)